2009
DOI: 10.1051/0004-6361/200810032
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic helicity accumulation and tilt angle evolution of newly emerging active regions

Abstract: Context. It has been known for years that there is a general dominance of negative (positive) helicity of active regions (ARs) in the northern (southern) solar hemisphere. For a better understanding of the role of helicity in the evolution of active regions, it is necessary to know more about the accumulation of helicity during the emergence of active regions. In particular, different conclusions were drawn in the past about the relationship between the accumulated helicity and the writhe of active regions. Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 46 publications
5
14
1
Order By: Relevance
“…Eq. (8)) comprised between 0.01 and 0.1 (LaBonte et al 2007;Jeong & Chae 2007;Tian & Alexander 2008;Yang et al 2009;Démoulin & Pariat 2009) which is several times smaller than the values obtained here. The emerging structure in the present simulation is thus injecting more twist into the coronal domain than typical active regions do.…”
Section: Conclusion and Discussioncontrasting
confidence: 79%
“…Eq. (8)) comprised between 0.01 and 0.1 (LaBonte et al 2007;Jeong & Chae 2007;Tian & Alexander 2008;Yang et al 2009;Démoulin & Pariat 2009) which is several times smaller than the values obtained here. The emerging structure in the present simulation is thus injecting more twist into the coronal domain than typical active regions do.…”
Section: Conclusion and Discussioncontrasting
confidence: 79%
“…Its sum over the emergence phase, normalized by the maximum magnetic flux to the second power, provides an estimation of the number of turns (of an equivalent uniformly twisted flux-tube). These estimations range from a few times 0.01 to a maximum value just above 0.1 (Nindos, Zhang, and Zhang, 2003;Liu and Zhang, 2006;Jeong and Chae, 2007;LaBonte, Georgoulis, and Rust, 2007;Tian and Alexander, 2008;Yang, Zhang, and Büchner, 2009). The magnetic helicity contained at a given time in the coronal field can also be estimated from magnetic-field extrapolations of the photospheric magnetograms, using the force-free model that best fits the observed coronal loops.…”
Section: Resultsmentioning
confidence: 96%
“…As Holder et al (2004) remark, Tian et al (2001) did not take out the mutual latitudinal dependence between twist and tilt, and therefore any signatures of writhing could have been suppressed in their data set. Nandy (2006), further analysing the dataset used by Holder et al (2004), as well as Yang et al (2009), analysed the twist-tilt relationship. For further details, see Section 3.4.…”
Section: Tilt Anglementioning
confidence: 99%
“…Luoni et al (2011) determined the helicity sign of 40 active regions during the emergence phase as inferred from the shape of the AR's magnetic tongues and found that 63% of southern hemisphere active regions follow the hemispheric trend and only 57% of regions in the northern hemisphere do. Yang et al (2009) found that 57.6% (56%) of emerging active regions in the southern (northern) hemisphere follow the helicity trend when using the method of Chae et al (2001) to determine the helicity of the region. In a study that involved a broader spectrum of active regions (not only emerging active regions), Pevtsov et al (1995) used the linear force-free field alpha-coefficient to determine the sign of helicity and found a stronger hemispheric helicity trend where 69% (75%) of northern (southern) regions had negative (positive) helicity.…”
Section: Magnetic Helictymentioning
confidence: 99%